Novel Scaffolds of Cell-Active Histone Demethylase Inhibitors Identified from High-Throughput Screening. (July 2015) - Wang, Wei; Marholz, Laura J.; Wang, Xiang
Jumonji C domain-containing histone demethylases (JHDMs) are epigenetic proteins capable of demethylating methylated lysine residues on histones proteins and for which high-quality chemical probes and eventual therapeutic leads are highly desirable. To expand the extent of known scaffolds targeting JHDMs, we initiated an unbiased high-throughput screening approach using a fluorescence polarization (FP)–based competitive binding assay we recently reported for JHDM1A (aka KDM2A). In total, 14, 400 compounds in the HitFinder collection v.11 were screened, which represent all the distinct skeletons of the Maybridge Library. An eventual three compounds with two new scaffolds were discovered and further validated, which not only show in vitro binding for two different JHDMs, JHDM1A and JMJD2A (aka KDM4A), but also induce hypermethylation of their substrate in cells. These represent novel scaffolds as JHDM inhibitors and provide a basis for future optimization of affinity and selectivity.